Manajemen Fisioterapi Dengan Pendekatan Neuro Developmental Treatment (NDT) Dan Passive Stretching Pada Kasus Cerebral Palsy Spastik Diplegi: Case Report - Vivian Jennie Diva Carissa; Totok Budi Santoso; Edy Waspada (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cerebral Palsy (CP) is a disorder of the immature and developing brain that causes impaired movement, posture and muscle strength. Spastic type represents 70% of cerebral palsy. The purpose of this study was to determine the effect of Neuro Developmental Treatment (NDT) on the patient's functional ability and the effect of Passive Stretching on reducing spasticity. The research method used in this study is single subject research involving a 3-year-old girl with a diagnosis of cerebral calsy spastic Diplegi. The interventions given were NDT and Passive Stretching. In this study, it was found that there was still no significant change in the level of muscle spasticity and gross motor with the condition of spastic diplegi cerebral palsy. In future research, the author hopes that this research will be conducted over a longer period of time to determine the effect of physiotherapy on children with a diagnosis of spastic diplegiate cerebral palsy.